A negligência no tratado “Da Educação da Criança” de Plutarco - Souza, Sílvio Cláudio Ferrari de (2021)
This research seeks to expose three points: 1. To present a brief contextualization of Plutarch's life and works; 2. Analyze the term neglect in the treatise “The Education of Child” by Plutarch and 3. Contextualize the reception of “The education of child” in the Renaissance, particularly in Juan Luis Vives. There are many negligences claimed by Plutarch in his Treaty: eugenics, the child's nutrition, the choice of “paidagogo”, the priority of “filois” parents, character formation, the irresponsibility of youth and others. In the Renaissance, Plutarch is among the Greek authors who most aroused interest, being the most read and imitated, translated and edited in the humanism of the Renaissance. The proposal for reception in Juan Luis Vives is based on some works in which the humanist deals exclusively with puerile education, and consists of an attempt to map in Vives the neglects pointed out by Plutarch in “The education of child”.